2004
DOI: 10.1159/000078570
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypic evolution in the Galliformes: An examination of the process of karyotypic evolution by comparison of the molecular cytogenetic findings with the molecular phylogeny

Abstract: To define the process of karyotypic evolution in the Galliformes on a molecular basis, we conducted genome-wide comparative chromosome painting for eight species, i.e. silver pheasant (Lophura nycthemera), Lady Amherst’s pheasant (Chrysolophus amherstiae), ring-necked pheasant (Phasianus colchicus), turkey (Meleagris gallopavo), Western capercaillie (Tetrao urogallus), Chinese bamboo-partridge (Bambusicola thoracica) and common peafowl (Pavo cristatus) of the Phasianidae, and plain chachalaca (Ortalis vetula) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
106
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(125 citation statements)
references
References 8 publications
16
106
3
Order By: Relevance
“…Chromosome painting with the GGA4 probe confirmed that the submetacentric chicken chromosome 4 resulted from a centric fusion between the ancestral type of acrocentric 13 chromosome 4 (GGA4q) and a smaller (GGA4p) (Shetty et al 1999, Shibusawa et al 2004b). The short arm of GGA4 is GC-rich, preserving the feature of GC-rich bird microchromosome (McQueen et al 1996(McQueen et al , 1998 Griffin et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromosome painting with the GGA4 probe confirmed that the submetacentric chicken chromosome 4 resulted from a centric fusion between the ancestral type of acrocentric 13 chromosome 4 (GGA4q) and a smaller (GGA4p) (Shetty et al 1999, Shibusawa et al 2004b). The short arm of GGA4 is GC-rich, preserving the feature of GC-rich bird microchromosome (McQueen et al 1996(McQueen et al , 1998 Griffin et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The short arm of GGA4 is GC-rich, preserving the feature of GC-rich bird microchromosome (McQueen et al 1996(McQueen et al , 1998 Griffin et al 2007). We previously delineated the process of karyotypic evolution of the Galliformes by comparing the chromosome painting data of 13 Galliformes species with their molecular phylogenetic tree constructed with the mitochondrial DNA sequences, and consequently proposed that the karyotype of emu is identical with the ancestral karyotype of the Galliformes (at least for the largest chromosome pairs) (Shibusawa et al 2004b). The 18S-28S rRNA genes were localized to a pair of undistinguishable microchromosomes in all the five Struthioniformes species like chicken with the rRNA genes located on chromosome 16, suggesting that the rRNA genes might have been located on a single pair of microchromosomes in the ancestral avian karyotype.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative cytogenetic analysis using FISH revealed the chromosome rearrangements of macrochromosomes between the chicken and Japanese quail (three pericentric inversions and one centromere repositioning) (Shibusawa et al, 2001) and between the chicken and pheasant (two interchromosomal rearrangements) (Shibusawa et al, 2004). However, a reduction in the number of spermatogonia and meiotic arrest at early prophase before the completion of chromosome synapsis have been commonly observed in F 1 hybrids between the chicken and the two species (Yamashina 1943a;Takashima and Mizuma, 1981), which suggests that the mechanism controlling sterility in these F 1 hybrids is due to genetic, rather than chromosomal incompatibilities between the parental species.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of chicken microchromosomes are acrocentric whereas quail microchromosomes are primarily submetacentric (Kaelbling and Fechheimer 1983;Calderón and Pigozzi 2006;Krasikova et al 2006Krasikova et al , 2009. Centromere positions on some macrochromosomes are also different (Ryttman and Tegelstrom 1981;Shibusawa et al 2001Shibusawa et al , 2004. First attempts to explain the discrepancy were done using high-resolution G-banding of metaphase chromosomes (Ryttman and Tegelstrom 1981;Sasaki 1981;Stock and Bunch 1982).…”
Section: Introductionmentioning
confidence: 99%